Relation of the Ankle Brachial Index (ABI) to left ventricular systolic function in patients with coronary artery disease - Abd Al-Majeed, Mahasen M.; Mohammed, Najeeb H.; Al Saffar, Hilal B. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Atherosclerosis is a diffuse disease process, being present in one vascular bed predicts its presence in the others. Ankle –Brachial Pressure Index (ABI) is a simple index related to the extent of atherosclerosis in coronary and noncoronary arterial beds, reflecting generalized atherosclerosis. Objectives: the aim of this study is to evaluate the relation of ABI to left ventricular systolic function using echocardiography in patients with coronary artery disease (CAD). Patients and Methods: Sixty seven patients (67) with CAD of either sex (70% males) with mean age 58± 6 years enrolled in this study, from December 2013 till May 2014; all were referred to the Iraqi Centre for Heart Disease (I.C.H.D.) for further evaluation and management. The ABI for each leg was calculated by dividing the lowest value of the ankle systolic blood pressure (SBP) (over both dorsalis pedis and posterior tibial arteries) by the highest value of either brachial SBP by using a Doppler ultrasound. The lower of the two values was used to define the patient ABI. The ejection fraction (EF) % and fractional shortening (FS) % were determined by using trans-thoracic echocardiography. Participants were divided into two groups according to ABI results: Group І: 29 patients with abnormal low ABI (ABI ≤ 0.90) with ABI mean of 0.79±0.12 and Group ІІ: 38 patients with normal ABI (0.9< ABI ≤1.30) with ABI mean of 1.03±0.10 as a control group. Results: There were no statistically significant differences in statistics between the two groups regarding risk factors for atherosclerosis. EF% was significantly lower in group I than those in group II in such a way that the mean values of EF% was 53.41±14.72 for group I vs. 63.11±8.93 for group II with the p value = 0.003. Also ABI is correlated with the severity of left ventricular systolic dysfunction. Conclusion: ABI is a useful bedside clinical test that predicts and assess left ventricular systolic dysfunction in patients with coronary artery disease.